Reproduksi Nilai Tradisi Walasuji Dalam Pembelajaran Karakter Di Era Disrupsi - Fernandes Carles; Nur Syahraeni; Andi Magfira Ranadhani; Ulmi Alfira; Afrina Selang; Nur Ilmi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
Walasuji Tradition is Buginise tradision in the province of South Sulawesi.  Walasuji is a protector for the Buginese women.  Buginese usually uses Walasuji tradition in the wedding procession.  Walasuji tradition has the meaning of social strata in the Walasuji layer fold.  There are philosophical values that reflect character values in the Walasuji.  This study aims to determine the values of the Walasuji tradition in Bugis society and to determine the values of the Walasuji tradition through storytelling by using animation media.  This study is descriptive research with a qualitative approach.  Data collection techniques are observation, interview, questionnaire, and documentation.  Data analysis techniques are reduction data and conclusion.  This study found there were five values of the Walasuji tradition, namely mutual cooperation, discipline, honesty, communication, and social care.  Based on the character values found in Walasuji through storytelling by using animation media.  Pretest results showed that only 40% of students knew the value of Walasuji, after treatment had been given, posttest results increased by 60%.  It can be concluded that the Walasuji tradition has character values that can be used as character learning media.